Hydrogen accumulation and distribution during the saturation of a VT1-0 titanium alloy by an electrolytic method and from a gas atmosphere; Technical Physics; Vol. 59, iss. 9 - Kudiyarov V. N. Victor Nikolaevich; Pushilina N. S. Natalia Sergeevna; Lider A. M. Andrey Markovich; Timchenko N. A. Nikolay Alekseevich (Physics Of Nanostructures, 2014)
Title screen